Auto handwash / Nur Aisyah Mohd Amin, Noraini Ahmad and Siti Khadijah Sanan - Mohd Amin, Nur Aisyah; Ahmad, Noraini; Sanan, Siti Khadijah (2013)
Nowadays, there are almost of the entire place example at restaurants, public houses, offices, school, colleges and universities have the hand washing tool. The functions of this tool are to washing and drying the hands. But normally this tools operating by semi automatic or manual. To give this tool can more systematic and particular, the Autohand Wash project are design for automatically washing and drying the hands. This project will design to combine three functions in one device which is the soap, water and dryer. The project consists of the microcontroller chip, an Light Dependent Resistor sensor and any other device. The main component that must be used to make sure an automatic hand washing and drying machine operating for automatically is microcontroller chip and the microcontroller chip that be used is PIC16F877A. This microcontroller used to control the whole machine which is water, soap and dryer. The LDR sensor are very useful especially in light or dark sensor circuits. When the LDR sensor detect the 'dark, the circuit will be function. So, a signal will be send to the PIC 16F877A. Then the PIC 16F877A will analyze the signal and the machine will operated whether produce water, soap or drying process will happen.